Plumage aberration observation in House Crow (Corvussplendens) in Coimbatore district of Tamil Nadu, India - Ashwin C.P; Arjun M.S; Angel Joy (Zenodo, 2022)
ABSTRACT Plumage anomalies in birds are more prevalent in India, where numerous studies have lately been published. We show an instance of brown plumage aberration in a Common House Crow ( Corvussplendens ) in this report. The plumage of the Common House Crow has been documented in a variety of morphs, the majority of which are examples of lucistic and other aberrations. However, the brown aberration observed by us was unusual and has been discussed. Key words: Plumage, brown, aberration, morphs, lucistic REFERENCES Arockianathan, Samson & Princy, J., 2020. A record on colour aberration in Fulvous-breasted Woodpecker in, Himachal Pradesh, India. Zoos' Print Journal 35: 42-44. Dharmakumarsinhji, R. S., 1975. A Whiteheaded duck. Newsletter for Birdwatchers 15(1): 9. Flood, R. L., & Van Grouw, H., 2015. Unfamiliar plumage types of Fulmars in the North Atlantic. Brit. Birds 108: 331-348. Forrest, S. C., & Naveen, R., 2000. Prevalence of leucism in pygocelid penguins of the Antarctic peninsula. Waterbirds , 283-285. Frainer, G., Daudt, N. W., & Carlos, C. J., 2015. Aberrantly plumaged White-chinned Petrels Procellaria aequinoctialis in the Brazilian waters, south-west Atlantic Ocean. Marine Biodiversity Records, 8. Hume, J. P., & van Grouw, H., 2014. Colour aberrations in extinct and endangered birds. Kale, T., 2006. White Crow on the bank of Ujani Dam. ‘Loksatta’ News Paper, Pune edition, 9 September 2006. Mahabal, A. N. I. L., Sharma, R. M., & Sayyed, A. M. I. T., 2015. Colour aberrations in Indian birds. Birding Asia 24: 19-121. Swapna Gurrapu and Estari Mamidala. In vitro HIV-Reverse Transcriptase Inhibition of Andrographolide Isolatedfrom Andrographis Paniculata. European Journal of Biomedical and Pharmaceutical Sciences. 2017. Volume 4, Issue 12. 516-522. Mancini, P. L., Jiménez, S., Neves, T., & Bugoni, L., 2010. Records of leucism in albatrosses and petrels (Procellariiformes) in the South Atlantic Ocean. Revista Brasileira de Ornitologia 18(3): 245-248. Owen, M., & Skimmings, ...